Gaya Hidup Konsumsi Kopi dan Implikasinya terhadap Insiden Hipertensi pada Calon Pendonor Darah - Rendi Ariyanto Sinanto; Eva Viaristin; Rudina Azimata Rosyidah; Windadari Murni Hartini (PT. Promosi Kesehatan Media, 2026)
ABSTRACT Background: Hypertension is a significant health problem and can affect a person's eligibility to donate blood. Elevated blood pressure can lead to serious health risks, including stroke and heart attack. One factor contributing to this increase is the caffeine in coffee, which is thought to increase blood pressure, so understanding its impact on potential donors is important. This study aims to analyze the relationship between coffee consumption and the incidence of hypertension among potential donors at the Indonesian Red Cross (PMI) Blood Donor Unit (UTD) in Yogyakarta City in 2025. Methods: The research method used was an analytical survey with a cross-sectional design, using primary data from questionnaires administered to donors. This study was conducted in January 2025 among donors at the PMI Blood Donor Unit (UTD) in Yogyakarta City. A sample of 65 respondents was selected using a purposive sampling technique using questionnaires and digital blood pressure monitors. Univariate and bivariate analyses used the Chi-Square test. Results and Discussion: The results showed that of the 65 respondents, 43 (66.2%) were moderate coffee consumers, 15 (23.1%) were high coffee consumers, and 7 (10.8%) were low coffee consumers. Respondents with no history of hypertension were 32 people (49.2%), with hypertension were 33 people (50.8%). The results of the Chi Square test analysis between coffee consumption and the incidence of hypertension in respondents showed that there was a significant relationship between coffee consumption and the incidence of hypertension in prospective donors at the UTD PMI Yogyakarta City in 2025 with a sig. value (two-sided) = 0.000 (<0.05). Conclusion: There is a significant relationship between coffee consumption and the incidence of hypertension in potential blood donors.